FAKTOR YANG MEMPENGARUHI EMOSI PESERTA DIDIK DI SMP NEGERI 26 PADANG - Lusiana, Zilvianda - (Bimbingan dan Konseling, 2014)
Problems studied in the field based on the phenomenon that is felt physical needs are notmet adequately, was wasted and not accepted by anyone including their own parents, feel muchhampered causing dissatisfaction, anxiety and resentment of their own destiny and lead touncontrolled emotions. The purpose of this study is to describe: 1) internal factors that influencethe emotions of learners, 2) external factors that affect the emotion of learners. This type ofresearch is descriptive quantitative method. The population was students of class VII, VIII and IXin SMP 26 Padang. The samples in this study using the cluster technique. Cluster totaling 85people. The instrument used for data collection in the form of a questionnaire. To analyze the dataused formula percentage.The results of this study revealed that the factors that influence theemotions of students at Junior High School 26 in Padang, in general internal factors in terms ofphysical changes to the criteria for many respondents (54.12%), and external factors in terms ofchanges in patterns of interaction with parents with many criteria with respondents of (64.71%),changes in interactions with peers with many criteria with respondents of (71.76%), changesoutside of the view of many criteria with respondents of (43.53%), and changes in the interactionwith the school with many criteria with respondents of (56.47%).